2013
DOI: 10.3233/nre-130995
|View full text |Cite
|
Sign up to set email alerts
|

A telerehabilitation program by virtual reality-video games improves balance and postural control in multiple sclerosis patients

Abstract: BACKGROUND: Balance and postural control (PC) disorders are frequent motor disorder symptoms associated with multiple sclerosis (MS). OBJECTIVE: To demonstrate the potential improvements in balance and PC among patients with MS who complete a virtual reality telerehabilitation program that represents a feasible alternative to physical therapy for situations in which conventional treatment is not available. METHODS: 50 patients was recruited. Control group (n = 25) received physiotherapy treatment twice a week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 29 publications
2
85
0
3
Order By: Relevance
“…The authors conducted an introduction seminar and a following internet-based e-training providing an online community to interact with others or a therapist in order to modify physical activity in daily living. Gutiérrez et al [ 41 ] examined the usefulness and effectiveness of a telerehabilitation program for PwMS using virtual reality-video games. The authors concluded that those virtual reality-video games might be a possible training therapeutic alternative if conventional treatment is not available [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors conducted an introduction seminar and a following internet-based e-training providing an online community to interact with others or a therapist in order to modify physical activity in daily living. Gutiérrez et al [ 41 ] examined the usefulness and effectiveness of a telerehabilitation program for PwMS using virtual reality-video games. The authors concluded that those virtual reality-video games might be a possible training therapeutic alternative if conventional treatment is not available [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gutiérrez et al [ 41 ] examined the usefulness and effectiveness of a telerehabilitation program for PwMS using virtual reality-video games. The authors concluded that those virtual reality-video games might be a possible training therapeutic alternative if conventional treatment is not available [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also found increased specific balance benefits of Kinect based telerehabilitation over standard rehabilitation [43,46], although both approaches led to improved general balance.…”
Section: Usingmentioning
confidence: 96%
“…Considering that balance and postural control are often impaired in Multiple Sclerosis [43] (MS), trials have been conducted in aims of assessing the efficacy of balance training in this pathology.…”
Section: Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation